2008
DOI: 10.1017/s0004972708000774
|View full text |Cite
|
Sign up to set email alerts
|

On a Recent Generalization of Semiperfect Rings

Abstract: In a recent paper by Wang and Ding, it was stated that any ring which is generalized supplemented as a left module over itself is semiperfect. The purpose of this note is to show that Wang and Ding's claim is not true and that the class of generalized supplemented rings lies properly between the classes of semilocal and semiperfect rings. Moreover, we propose a corrected version of the theorem by introducing a wider notion of 'local' for submodules.2000 Mathematics subject classification: primary 16L30; second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…By (ii), there exists a submodule E of L such that E is a Rad-supplement of K in M . By [3,Lemma 3.3], E is a w-local submodule of L. Note that U = U + E, since otherwise we have E ⊆ U ⊆ K and K = K + E = M . It follows that M = U + E + F for some element F ∈ S. But E + F ∈ S, a contradiction.…”
Section: Amply Rad-supplemented Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…By (ii), there exists a submodule E of L such that E is a Rad-supplement of K in M . By [3,Lemma 3.3], E is a w-local submodule of L. Note that U = U + E, since otherwise we have E ⊆ U ⊆ K and K = K + E = M . It follows that M = U + E + F for some element F ∈ S. But E + F ∈ S, a contradiction.…”
Section: Amply Rad-supplemented Modulesmentioning
confidence: 99%
“…w-local modules were first studied by Ware in [18], Gerasimov and Sakhaev in [8]. In [3], Büyükaşik and Lomp showed that this type of modules play a key role in the study of Rad-supplemented modules. This role is as important as the role played by local modules for supplemented modules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let M be an R-module and U , V be submodules of M . V is called a generalized supplement ( [1], [9], [11]…”
Section: Introductionmentioning
confidence: 99%
“…Clearly supplemented modules are cofinitely supplemented and weakly supplemented modules are cofinitely weak supplemented. M is called cofinitely generalized supplemented if every cofinite submodule of M has a generalized supplement (see [3]). Since every submodule of a finitely generated module is cofinite, a finitely generated module is generalized supplemented if and only if it is cofinitely generalized supplemented.…”
Section: Introductionmentioning
confidence: 99%